Short telomere length as a biomarker risk of lung cancer development induced by high radon levels: A pilot study - Narongchai Autsavapromporn (2018)
© 2018 by the authors. Licensee MDPI, Basel, Switzerland. Long-term exposure to radon has been determined to be the second leading cause of lung cancer after tobacco smoking. However, an in-depth study of this topic has not been explicitly carried out in Chiang Mai (Thailand). This paper presents the results of an indoor radon level measurement campaign in dwellings of Chiang Mai using total of 110 detectors (CR-39) during one year. The results show that the average radon levels varied from 35 to 219 Bq/m3, with an overall average of 57 Bq/m3. The finding also shows that the average value is higher than the global average value of 39 Bq/m3. In addition, to examine the cause of lung cancer development among people with risk of chronic exposure to radon during their lifetime, 35 non-smoker lung cancer patients and 33 healthy nonsmokers were analyzed for telomere length. As expected, telomere length was significantly shorter in lung cancer patients than in healthy nonsmokers. Among healthy nonsmokers, the telomere length was significantly shorter in a high radon group than in an unaffected low radon group. To the best of our knowledge, our research provides the first attempt in describing the shortened telomeres in areas with high levels of environmental radon that might be related to lung cancer development.